Angiocrine FSTL1 (Follistatin-Like Protein 1) Insufficiency Leads to Atrial and Venous Wall Fibrosis via SMAD3 Activation. Issue 4 (April 2020) - Jiang, Haijuan; Zhang, Luqing; Liu, Xuelian; Sun, Wei; Kato, Katsuhiro; Chen, Chuankai; Li, Xiao; Li, Taotao; Sun, Zhiliang; Han, Wencan; Zhang, Fujing; Xiao, Qi; et al.
Abstract : Objective: Angiocrine factors, mediating the endothelial-mural cell interaction in vascular wall construction as well as maintenance, are incompletely characterized. This study aims to investigate the role of endothelial cell–derived FSTL1 (follistatin-like protein 1) in vascular homeostasis. Approach and Results: Using conditional knockout mouse models, we show that loss of FSTL1 in endothelial cells ( Fstl1 ECKO ) led to an increase of pulmonary vascular resistance, resulting in the heart regurgitation especially with tricuspid valves. However, this abnormality was not detected in mutant mice with Fstl1 knockout in smooth muscle cells or hematopoietic cells. We further showed that there was excessive αSMA (α-smooth muscle actin) associated with atrial endocardia, heart valves, veins, and microvessels after the endothelial FSTL1 deletion. There was also an increase in collagen deposition, as demonstrated in livers of Fstl1 ECKO mutants. The SMAD3 (mothers against decapentaplegic homolog 3) phosphorylation (pSMAD3) was significantly enhanced, and pSMAD3 staining was colocalized with αSMA in vein walls, suggesting the activation of TGFβ (transforming growth factor β) signaling in vascular mural cells of Fstl1 ECKO mice. Consistently, treatment with a TGFβ pathway inhibitor reduced the abnormal association of αSMA with the atria and blood vessels in Fstl1 ECKO mutant mice. Conclusions: The findings imply that endothelial FSTL1 is critical for the homeostasis of vascular walls, and its insufficiency may favor cardiovascular fibrosis leading to heart failure. Abstract : Supplemental Digital Content is available in the text.